Happiness in Islam and Influencing Factors (SLR Approach) - Ranti Wiliasih; Hermanto Siregar; Tony Irawan; Irfan Syauqi Beik (Department of Islamic Economics, IPB University, 2024)
Islam is a religion that commands humans to pursue happiness both here and hereafter. Previous research states that many factors can influence happiness. However, these factors emphasize worldly happiness which is temporary, while the goal that humans want to achieve is not only happiness in this world but true happiness in the hereafter. This study explores the factors that influence individual happiness and examines the impact of faith and other factors on happiness. This research uses a systematic literature review method, precisely the Prisma method and has identified 3540 research results from Google Scholar, and screened into 1265 documents, then into 99 and selected 87 qualifying studies. The results of the analysis of this number of documents found that happiness in Islam is divided into temporary and true happiness, here and hereafter. Happiness is influenced by material factors, and non-material factors such as faith and other religiosity behaviors. Happiness derived from material factors is temporary, while religiosity factors such as faith, the practice of Sufism and religious behavior bring a sense of closeness to God, and provide tranquility and peace, which is an indication of true happiness.